Yangzhou and Quanzhou: Ongoing Research on Syro-Turkic Inscriptions - Franzmann, Majella (Lit Verlag GmbH&Co. KG Wien, 2013)
Syriac Christianity spread along the Silk Road together with Aramaic culture and liturgy. The staging posts of Christian merchants along the trade routes grew into first missionary centers. Thus, the mission of the Church of the East stretched from Persia to Arabia and India; and from the Oxus River to the Chinese shores. This volume contains a collection of studies on the Church of the East in its historical setting. Contributors have shed new light on this subject from various perspectives and academic disciplines, providing fresh insights into the rich heritage of Syriac Christianity.